Dracocephalum jacutense Peschkova from Yakutia: Extraction and Mass Spectrometric Characterization of 128 Chemical Compounds - Zhanna M. Okhlopkova; Mayya P. Razgonova; Zoya G. Rozhina; Polina S. Egorova; Kirill S. Golokhvast (Molecules, 2023)
Dracocephalum jacutense Peschkova is a rare and endangered species of the genus Dracocephalum of the Lamiaceae family. The species was first described in 1997 and listed in the Red Data Book of Yakutia. Significant differences in the multicomponent composition of extracts from D. jacutense collected in the natural environment and successfully introduced in the Botanical Garden of Yakutsk were identified by a team of authors earlier in a large study. In this work, we studied the chemical composition of the leaves, stem, and inflorescences of D. jacutense using the tandem mass spectrometry method. Only three cenopopulations of D. jacutense were found by us in the territory of the early habitat—in the vicinity of the village of Sangar, Kobyaysky district of Yakutia. The aboveground phytomass of the plant was collected, processed and dried as separate parts of the plant: inflorescences, stem and leaves. Firstly, a total of 128 compounds, 70% of which are polyphenols, were tentatively identified in extracts of D. jacutense. These polyphenol compounds were classified as 32 flavones, 12 flavonols, 6 flavan-3-ols, 7 flavanones, 17 phenolic acids, 2 lignans, 1 dihydrochalcone, 4 coumarins, and 8 anthocyanidins. Other chemical groups were presented as carotenoids, omega-3-fatty acids, omega-5-fatty acids, amino acids, purines, alkaloids, and sterols. The inflorescences are the richest in polyphenols (73 polyphenolic compounds were identified), while 33 and 22 polyphenols were found in the leaves and stems, respectively. A high level of identity for polyphenolic compounds in different parts of the plant is noted for flavanones (80%), followed by flavonols (25%), phenolic acids (15%), and flavones (13%). Furthermore, 78 compounds were identified for the first time in representatives of the genus Dracocephalum, including 50 polyphenolic compounds and 28 compounds of other chemical groups. The obtained results testify to the unique composition of polyphenolic compounds in different parts of D. jacutense.